A PSYCHOEDUCATION AS A MECHANISM FOR TRANSFORMING CAREGIVER BEHAVIOR IN THE CARE OF PEOPLE WITH MENTAL DISORDERS - Osep Yasier Almunsiri; Fadilah Lailatul; Rosyidah Alif Nurul (Journal of Smart Nursing and Health Science, 2026)
Background: Mental disorders are health problems that affect not only the patient, but also the family as a caregiver in long-term care. Caregivers have an important role in ensuring therapy adherence and supporting the patient's recovery. The behavior of caregivers in caring for people with mental disorders can be influenced by psychoeducation and family support. Purpose: To examine the role of psychoeducation in shaping caregiver behavior in the families of people with mental disorders. Method: This study uses a conceptual descriptive approach by reviewing various scientific literature from international and national journals relevant to psychoeducation, caregiver, and treatment of mental disorders. Results: The results of the study show that psychoeducation plays a role in increasing caregiver knowledge, forming a more adaptive perception, and influencing caregivers' attitudes in caring for patients. These changes have an impact on the formation of more effective care behaviors. Family support also plays a role as a reinforcing factor in improving caregiver behavior. Conclusion: Psychoeducation has an important role in shaping caregiver behavior through improving knowledge, perception, and attitudes. Family support strengthens the effectiveness of psychoeducation in the treatment of people with mental disorders.